Conflitti religiosi e filologia: heur et malheur dell'eremetismo: Isaac Casaubon contro Ermete Trismegisto - Scarpi, Paolo (Studi e materiali di storia delle religioni, 2017)
As regards the Hermetic tradition, A.D. Nock and Father A.-J. Festugière's edition of the Hermetic writings represents the philologically most reliable (in fact, the only one) edition available so far. However, this edition does not exactly do justice to the wide and complex Hermetic cultural tradition, which served as foundation for many important moments in western history, in particular the Renaissance period. Father Festugière, who devoted his whole life to the study of the Hermetic tradition, tried to complete the demolition job of the cultural outcome of the Hermetic texts carried out, for different reasons and with a different perspective, by the Calvinist Isaac Casaubon. It is known that Casaubon, on the verge of abjuring Calvinism while under the protection of Henry IV of France, was pushed to do so by James vi and I. Casaubon was not pushed to go against the Hermetic texts themselves, but rather against the use thereof made by Roman Catholicism, as expressed within the oeuvre of Cardinal Baronius. Following Casaubon's De rebus sacris et ecclesiasticis, and in spite of occasional attempts at rehabilitation, the Hermetic treatises have often been looked at with great suspicion